Androgen receptor binding to an androgen‐responsive element in the promoter of the Srsf4 gene inhibits its expression in mouse Sertoli cells. Issue 12 (3rd September 2015) - Guo, Huan; Li, Yuchi; Luo, Manling; Lin, Shouren; Chen, Jianbo; Ma, Qian; Gu, Yanli; Jiang, Zhimao; Gui, Yaoting
SUMMARY: The serine/arginine‐rich splicing actor 4 ( SRSF4 ) is essential for pre‐mRNA splicing and can influence alternative‐splice‐site choice. Little is known about the specific function of this gene in the reproductive system, although a recent study identified a SRSF4 polymorphism significantly associated with a decreased risk of non‐obstructive azoospermia in Chinese men. We previously found that the expression of Srsf4 was up‐regulated in the testes of Sertoli‐cell‐selective androgen receptor knockout (S‐ Ar −/y ) mice compared to wild‐type mice using digital gene expression analysis. In this study, we confirmed and extended the selective gene expression data: SRSF4 was mainly located in the nucleus of Sertoli cells, and Srsf4 expression in the Sertoli‐cell‐derived cell line TM4 is down‐regulation by testosterone. Moreover, androgen receptor directly binds the androgen‐responsive element of the Srsf4 promoter. Taken together, these results demonstrate that Srsf4 is a direct downstream target of the androgen receptor in mouse Sertoli cells. Mol. Reprod. Dev. 82: 976–985, 2015. © 2015 Wiley Periodicals, Inc .